2023
DOI: 10.3389/fpls.2022.1017983
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping identifies novel major loci for kernel row number-associated ear fasciation, ear prolificacy and tillering in maize (Zea mays L.)

Abstract: Maize ear fasciation originates from excessive or abnormal proliferation of the ear meristem and usually manifests as flattened multiple-tipped ear and/or disordered kernel arrangement. Ear prolificacy expresses as multiple ears per plant or per node. Both ear fasciation and prolificacy can affect grain yield. The genetic control of the two traits was studied using two recombinant inbred line populations (B73 × Lo1016 and Lo964 × Lo1016) with Lo1016 and Lo964 as donors of ear fasciation and prolificacy, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
1
1
2
Order By: Relevance
“…The functions of these genes were consistent with those of the GO-and KEGG-enriched pathways. Although previous researchers have identified KRN-associated QTLs on the same chromosomes as in this study [16,85], the physical locations of these KRN-associated QTLs were different. Therefore, we believe that the candidate genes identified in this study are distinct from those reported in previous studies and represent novel candidate genes associated with KRN.…”
Section: Co-located Genes Were Confirmed To Be Associated With Krncontrasting
confidence: 55%
“…The functions of these genes were consistent with those of the GO-and KEGG-enriched pathways. Although previous researchers have identified KRN-associated QTLs on the same chromosomes as in this study [16,85], the physical locations of these KRN-associated QTLs were different. Therefore, we believe that the candidate genes identified in this study are distinct from those reported in previous studies and represent novel candidate genes associated with KRN.…”
Section: Co-located Genes Were Confirmed To Be Associated With Krncontrasting
confidence: 55%
“…Виявлено корелятивні зв'язки між молекулярно-генетичними процесами та морфологічними змінами, які призводять до виникнення фасціацій та інших анoмалій (Meyerowitz et al, 1989;Fletcher, 2002). На думку дослідників, сучасна тератологія як розділ морфології вийшла за межі простого фіксування та опису тератологічних феноменів і перейшла в площину моделювання процесів розвитку та мутаційного аналізу, надаючи корисну інформацію для програм селекції за допомогою геноміки (Li et al, 2023).…”
Section: вступunclassified
“…Виявлені тератоморфи підтверджують, що аномалії розвитку та брунькові мутації -це складні фізіологічні процеси, обумовлені порушенням диференціації апікальної меристеми органів рослин, які можуть бути спричинені багатьма факторами: коливанням температури та вологості, дією хімічних і радіоактивних реагентів, патогенними мікроорганізмами (Sim et al, 2004;Yan еt al., 2016;Madhupriya еt al., 2017;Li et al, 2023).…”
Section: аномалії пов'язані з порушенням нормальної форми та функції ...unclassified
“…Currently, with the development of molecular marker technologies, genetic localization using GWAS and QTL analysis has been widely used in molecular breeding [10][11][12][13][14]. This has helped reveal the genetic mechanisms of many quantitative traits, such as kernel row number, growth period, KNR, etc., and has facilitated the genetic improvement of these traits [15]. Genes such as inflorescence gene EAD1 [16], Thick tassel dwarf1 (td1) [17], fasciated ear 2 (fea2) and clavate 3/embryo surrounding region-related7 (cle7) [18], compact plant 2 (ct2) [19], fasciated ear3 (fea3) [20], ramose locus2 (rel2) [21], and fon2-like CLE protein 1 (fcp1) [22] can regulate the development of spikelet pair meristems (SPMs) and spike meristems (SMs).…”
Section: Introductionmentioning
confidence: 99%